ANALISA KADAR TIMBAL (Pb) PADA HATI SAPI DARI PETERNAKAN SAPI POTONG DI KABUPATEN DELISERDANG TAHUN 2012 - Merry Irasanti; Devi Nuraini Santi; Surya Dharma (Lingkungan dan Kesehatan Kerja, 2013)
Analysis of lead (Pb) in beef liver from cattle farm in Deliserdang regency in 2012. Beef liver is a nutritious food contains a lot of protein needed for body growth, development and health. A high protein beef liver could be potentially contaminated both microbiological and chemical substance. Contamination of lead (Pb) could be occurred at the husbandry.This study aimed to determine the lead (Pb) in beef liver from cattle farm in Deli Serdang and describe the location of the cattle farm, fodder and drinking water for cow. This study was conducted by descriptive method as an attempt to describe the location of the cattle farm, fodder and drinking water for cow and the analysis of the lead (Pb) in beef liver. The analyze showed the lead (Pb) in beef liver did not exceed the specified threshold value, according to Standar Nasional Indonesia 7378 tahun 2009. The laboratory tests result of the lead (Pb) from ten beef livers showed that the lowest was 0,023 ppm and the highest was 1,230 ppm. Based on the result of study, it was found that the content of lead (Pb) in beef liver was under the specified threshold value. This could be as the result of the good feeding of cattle farm in Deli Serdang regency but there are also many cattle farms located on the side of the highway and close to waste dumps. However, there should be controlling, regulation, and advisory by related instance (Health Department). Key words : Lead (Pb), beef liver